Hemodynamic Determinants of Myocardial B-Type Natriuretic Peptide Release - Micha T. Maeder; Justin A. Mariani; David M. Kaye (2010)
Although B-type natriuretic peptide (BNP) is widely used as a biomarker for heart failure, the in vivo mechanical stimulus for its cardiac release remains poorly defined. We aimed to characterize the hemodynamic determinants of the transcardiac BNP gradient as a measure of myocardial BNP release by performing a detailed hemodynamic assessment in subjects with a broad spectrum of systolic and diastolic left ventricular dysfunction. Forty-two subjects underwent a detailed transthoracic echocardiographic study, right heart catheterization, and simultaneous BNP measurement in arterial and coronary sinus plasma. The transcardiac BNP gradient was lowest in subjects with normal left ventricular ejection fraction/high peak early diastolic annular velocity (n=11), intermediate in those with normal left ventricular ejection fraction/low peak early diastolic annular velocity (n=13), and highest in those with low left ventricular ejection fraction/low peak early diastolic annular velocity (n=18; 29 ng/L (range: 15 to 78 ng/L) versus 88 ng/L (range: 34 to 172 ng/L) versus 1566 ng/L (range: 624 to 2349 ng/L; P<0.001). Across the range of patients, left ventricular end-systolic wall stress (r(2)=0.51) and peak systolic mitral annular velocity (r(2)=0.47) showed the strongest correlation with higher transcardiac BNP gradient. In contrast, the transcardiac BNP gradient was weakly related to indices of diastolic load, including pulmonary capillary wedge pressure (r(2)=0.27) and left ventricular end-diastolic wall stress (r(2)=0.21). Across this spectrum of pathophysiology, left ventricular end-systolic wall stress appears to be the key mechanical stimulus influencing cardiac BNP release.